2003
DOI: 10.1080/14017430310015406
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine as an additive to crystalloid cardioplegia increased oxidative stress capacity in CABG patients

Abstract: NAC increased tissue capacity against oxidative stress and decreased inflammatory response in CABG patients with normal ejection fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…Consistent with our own results, Karu et al showed that the oxidative stress (oxidized glutathione measurement) is not predictive of early postoperative left ventricular contractile function [31]. Our results are also in accordance with other reports showing no significant differences in invasive hemodynamic data between groups when different antioxidants (pyruvate, N-acetylcysteine) were added to crystalloid or blood cardioplegia solutions [32,33]. It is possible that this experimental model causes an activation of leukocytes in blood cardioplegia, which induces inflammation and histologic abnormalities [19], but these lesions are also found in the group with crystalloid cardioplegia and static storage.…”
Section: Discussionsupporting
confidence: 96%
“…Consistent with our own results, Karu et al showed that the oxidative stress (oxidized glutathione measurement) is not predictive of early postoperative left ventricular contractile function [31]. Our results are also in accordance with other reports showing no significant differences in invasive hemodynamic data between groups when different antioxidants (pyruvate, N-acetylcysteine) were added to crystalloid or blood cardioplegia solutions [32,33]. It is possible that this experimental model causes an activation of leukocytes in blood cardioplegia, which induces inflammation and histologic abnormalities [19], but these lesions are also found in the group with crystalloid cardioplegia and static storage.…”
Section: Discussionsupporting
confidence: 96%
“…Such patients are, for instance, those with hepatic failure awaiting a liver transplantation, and those scheduled for heart surgery. A recent study found increased postoperative blood loss in patients receiving NAC as an additive to crystalloid cardioplegia [18].…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective efficacy of NAC in cardiac surgery has been reported in a number of recent studies [24][25][26] . However, a considerable number of studies have concluded that the use of NAC in cardiac surgery did not appear to bestow any statistically significant benefits [27,28] .…”
Section: Discussionmentioning
confidence: 99%